Detection of a novel gross deletion in the UNC13D gene ends the diagnostic odyssey for a family with familial hemophagocytic lymphohistiocytosis 3 - Chinmayee B. Nagaraj; Diana S. Brightman; Hannah Rea; Emily Wakefield; Nina V. G. Harkavy; Lisa Dyer; Wenying Zhang (BMC, 2024)
Abstract Background Familial hemophagocytic lymphohistiocytosis (FHL) is an immunological disorder characterized by overactivation of macrophages and T lymphocytes. This autosomal recessive condition has been characterized into multiple types depending on the genetic etiology. FHL type 3 is associated with bi-allelic pathogenic variants in the UNC13D gene. Case presentation We present a 12-year diagnostic odyssey for a family with FHL that signifies the advances of FHL genetic testing in a clinical genetic diagnostic laboratory setting. We describe the first case of a large UNC13D gross deletion in trans to a nonsense variant in a family with FHL3, which may have been mediated by Alu elements within introns 12 and 25 of the UNC13D gene. Conclusions This case highlights the importance of re-evaluating past genetic testing for a patient and family as test technology evolves in order to end a diagnostic odyssey.